2011
DOI: 10.1093/eurheartj/ehr473
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the 3′ untranslated region of the KCNQ1-encoded Kv7.1 potassium channel modify disease severity in patients with type 1 long QT syndrome in an allele-specific manner

Abstract: AimsHeterozygous mutations in KCNQ1 cause type 1 long QT syndrome (LQT1), a disease characterized by prolonged heart rate-corrected QT interval (QTc) and life-threatening arrhythmias. It is unknown why disease penetrance and expressivity is so variable between individuals hosting identical mutations. We aimed to study whether this can be explained by single nucleotide polymorphisms (SNPs) in KCNQ1's 3′ untranslated region (3′UTR).Methods and resultsThis study was performed in 84 LQT1 patients from the Academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 16 publications
3
83
0
2
Order By: Relevance
“…An overview of known miRNAs affecting cardiac potassium currents is given in Adding another level of complexity, Amin et al (12) reported that common variants in the 3'-UTR of the KCNQ1 gene encoding K V 7.1 modified disease severity in LQTS patients in an allele-specific manner. As K V 7.1 channels are composed of tetramers, in a heterozygous mutation carrier channels will be formed from two healthy and two mutant subunits, provided that wild-type and mutant alleles are expressed equally well.…”
Section: Posttranscriptional Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of known miRNAs affecting cardiac potassium currents is given in Adding another level of complexity, Amin et al (12) reported that common variants in the 3'-UTR of the KCNQ1 gene encoding K V 7.1 modified disease severity in LQTS patients in an allele-specific manner. As K V 7.1 channels are composed of tetramers, in a heterozygous mutation carrier channels will be formed from two healthy and two mutant subunits, provided that wild-type and mutant alleles are expressed equally well.…”
Section: Posttranscriptional Mechanismsmentioning
confidence: 99%
“…Depending on which nucleotide sequence favors the binding of miRNAs, then the balance of wild-type and mutant subunits relies on whether the "suppressive" SNP variants reside on the normal or mutant allele. Accordingly, an increased expression of the mutant allele would enhance the disease phenotype of the patient, while an increased expression of the wild-type allele could possibly result in an asymptomatic phenotype (12).…”
Section: Posttranscriptional Mechanismsmentioning
confidence: 99%
“…), and is associated with various physiological functions (cardiocyte repolarization, gastric acidification, electrolyte excretion/reabsorption, etc.) (Schroeder et al, 2000;Vallon et al, 2001Vallon et al, , 2005Warth et al, 2002;Lang et al, 2007;Yang et al, 2007;Das et al, 2009;Pan et al, 2010;Amin et al, 2012;Sung et al, 2014). In the mouse kidney, KCNQ1 mRNA is expressed in the PT, DCT, CNT, CD, and glomeruli (Wang, 2004;Zheng et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mutations in the KCNQ1 gene have been associated with human Romano-Ward or long QT syndrome (OMIM: No. 192500) (Amin et al, 2012), Jervell and Lange-Nielsen syndrome (OMIM: No. 220400) (Sung et al, 2014), familial atrial fibrillation (Das et al, 2009), and atrioventricular block (Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The 5′-flanking region of the gene, particularly the minimal promoter, is the key transcriptional regulatory region in gene expression (Saeki et al 2011, Amin et al 2012. SNPs in the promoter region may modify the transcription factor binding sites, thereby affecting gene expression (Pan et al 2013, Zhang et al 2015.…”
Section: Introductionmentioning
confidence: 99%